2004
DOI: 10.1200/jco.2004.03.136
|View full text |Cite
|
Sign up to set email alerts
|

Use of Metaphor in the Discourse on Cancer

Abstract: I'm going to kill you. Every day, I'm going to kill you, and then I'm going to bring you back to life. We're going to hit you with chemo, and then hit you again, and hit you again. You're not going to be able to walk. We're practically going to have to teach you to walk again after we're done." Anonymous Oncologist 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(206 citation statements)
references
References 11 publications
(8 reference statements)
1
194
2
9
Order By: Relevance
“…For example, cancer is re-currently described as allowing for new understanding in terms of clearing vision (It allowed me to see life in a different way, It was like putting on a new pair of glasses), which can be understood as an instantiation of the conventional metaphor "understanding is seeing". Subsequent work has highlighted other conventional metaphors in patients' descriptions of cancer experiences, such as the "martial" and "journey" metaphors described by Reisfeld and Wilson (2004).…”
Section: Metaphor In Linguistics and Health Communicationmentioning
confidence: 99%
“…For example, cancer is re-currently described as allowing for new understanding in terms of clearing vision (It allowed me to see life in a different way, It was like putting on a new pair of glasses), which can be understood as an instantiation of the conventional metaphor "understanding is seeing". Subsequent work has highlighted other conventional metaphors in patients' descriptions of cancer experiences, such as the "martial" and "journey" metaphors described by Reisfeld and Wilson (2004).…”
Section: Metaphor In Linguistics and Health Communicationmentioning
confidence: 99%
“…This is despite the fact that much of the scientific research highlighted in the printed press over the five year time frame of this study was still in development and often untested in humans. Terms such as 'attack' , 'destroying' , 'struggle' , and 'battle' , which were readily written by journalists in reference to RA, seemed to draw on metaphors of warfare [57][58][59]. Lakoff and Johnson [60] have suggested that conceptual systems are designed to function in a metaphorical sense.…”
Section: Discussionmentioning
confidence: 99%
“…That is, metaphors allow us to communicate concepts that are abstract or complex in simplified terms [60]. Metaphoric language has a long and durable history in medicine [57][58][59]61]. Metaphors of transgression and punishment have been commonly used in tuberculosis (TB) research and clinical practice [61], and military metaphors are a noticeable feature of discourses around the medical treatment of cancer [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…They are a means of generating ideas, promoting creativity, and constructing concepts and theories. Thinking based on metaphors and comparisons is a way of transforming a concept into something that is so suggestive, interesting, and surprising, that it reaches people more easily [11][12][13][14][15].…”
Section: Commentarymentioning
confidence: 99%